MENUMBUHKAN KEMANDIRIAN ANAK : BELAJAR KEIKHLASAN HIDUP SANTRI PONDOK PESANTREN MIFTAHUL FALAH SRIWIJAYA BANDAR MATARAM LAMPUNG TENGAH - Syaifur Rohman (Aplikasia: Jurnal Aplikasi Ilmu-ilmu Agama, 2021)
Pesantren not only teach about knowledge in ink that can be read but also in the form of behavior that can be seen and practiced in life. The spirit of the pesantren which prioritizes morality over science encourages every activity in the pesantren to be carried out on the basis of the formation of good character. Among the good characters that are widely taught in the pesantren are an independent and sincere attitude. This is considering that pesantren is a crater of ‘candradimuka’ which function is to prepare future generations of a strong nation. Independence absolutely must be possessed by the younger generation so they are able to survive in the modern era. One of the pesantren that implements and instills attitudes of independence to its students is the Miftahul Falah Islamic boarding school under Kyai Sirajul Munir's care. This cottage teaches independence to its students with various entrepreneurial activities so the students have certain skills ranging fisheries, agriculture, fashion, and trade. By equipping independent attitudes in students as early as possible, students are able to analyze the condition of the surrounding community and provide solutions that they can do for their future problems. Independence based on an attitude of sincerity has shaped the personality of santri at the Miftahul Falah Islamic boarding school to stand and to be independent in taking education without burdening their parents.